Advertising and VR: regulatory challenges ahead. Issue 1 (June 2018) - Lobov, Kostyantyn
Abstract : As virtual reality (VR) products increase in popularity, stakeholders in the games industry wanting to promote their VR products, or to leverage VR technology for advertising more generally, need to be aware of the most common legal and regulatory pitfalls, particularly as this is an area in which advertising and consumer protection regulators are likely to take a keen interest. Meanwhile, the regulators themselves will also have to be agile. They face the challenge of having to apply laws and self-regulatory codes which were not drafted with VR technology in mind to new situations, in a fair and rational manner which does not expose them to the risk of judicial review.